Increased Incidence of Tinnitus Following a Hyperthyroidism Diagnosis: A Population-Based Longitudinal Study - Wang, Tang-Chuan; Chiu, Chien-Jen; Chen, Pei-Chun; Chang, Ta-Yuan; Tyler, Richard S.; Rojas-Roncancio, Eveling; Coelho, Claudia Barros; Mancini, Patricia C.; Lin, Cheng-Li; Lin, Chia-Der; Tsai, Ming-Hsui (Frontiers in Endocrinology, 2021)
Background: An association between thyroid disease and tinnitus has been described previously but further longitudinal, population-based studies are limited. Objective: To investigate the incidence of tinnitus in patients with hyperthyroidism in a national sample, and to identify risk level and associated factors for tinnitus in hyperthyroidism patients. Design: Retrospective cohort study. Patient data were collected from the Longitudinal Health Insurance Database (LHID 2000), which includes national claims data of patient expenditures for admissions or ambulatory care from 1996 to 2011. Setting: Taiwan hospitals and clinics providing healthcare nationwide. Participants: Patients aged 20 years and older with newly diagnosed hyperthyroidism (ICD-9-CM code 242) between 2000-2010 were selected as the study cohort. Hyperthyroidism patient cohort were identified from the LHID2000. Those with tinnitus history (ICD-9-CM code 388.3) before the index date (first hyperthyroidism diagnosis), younger than 20 years, and with incomplete demographic data were excluded. The non-hyperthyroidism cohort included patients with no history of hyperthyroidism and no documented tinnitus. Main outcomes and measures: Incidence of tinnitus was the primary outcome. Baseline demographic factors and comorbidities possibly associated with tinnitus, including age, sex, and comorbidities of hearing loss, vertigo, insomnia and anxiety, were retrieved from the LHID 2000. Patients were followed until end of 2011. Results: During the study period, 780 (4.9%) hyperthyroidism patients and 2007 (3.2%) non-hyperthyroidism controls developed tinnitus. Incidence rate of tinnitus in the hyperthyroidism cohort was significantly higher in hyperthyroidism cohort (7.86 vs. 5.05 per 1000 person-years) than that in non-hyperthyroidism cohort. A higher proportion of patients with hyperthyroidism had comorbid insomnia (45.1％ vs. 30.9％) and anxiety (14.0％ vs. 5.73％) than those without hyperthyroidism. After adjusting for age, gender and comorbidities (vertigo, insomnia, anxiety, hearing loss), hyperthyroidism patients had 1.38-fold higher risk of tinnitus (95% CI = 1.27-1.50) than those without hyperthyroidism. Conclusions: This large population-based study suggests patients with diagnosed hyperthyroidism was more prone to develop tinnitus. Our findings suggest evaluation for comorbid vertigo, insomnia, anxiety and/or hearing loss may identify patients who are at high risk of developing tinnitus in patients with hyperthyroidism.